Study On The Solubility And Foaming OfC02 In Aqueous Amine Solutions - Mohamad Akhir, Norlizayani (Universiti Teknologi Petronas, 2005)
The desire to alleviate the problem of global warming has resulted in environmental concern over a reduction of greenhouse emission especially CO2 from industrial sources. The removal of CO2 from natural gas purification and petrochemicals manufacturing is a very important operation in industry. Absorption with amine-based absorbents is the most common technology for CO2 removal today. In view of this, many research works have been done to determine the CO2 solubility in different types of amines at different temperatures and pressures and to identify the way to reduce its operational problems such as foaming. The objectives of this experimental based project, 'Study on the solubility and foaming of CO2 in aqueous amine solutions' are to determine the CO2 loading capacity in selected single and mixed amine solutions at different temperatures and foaming tendency of CO2 absorption in amine solutions. This study focused on the CO2 solubility in primary, secondary and tertiary amines and also mixture of these amines with variation of temperature and concentration. The method used for the solubility test is by directing the CO2 and N2 gas into the conical flask that contains amine solution and the outlet gas is analyzed by IR Gas Analyzer to determine the CO2 slippage. In the foaming test, a small amount of petrol as the source of contaminant is added into the amine solution. The height of the foam and its foaming phenomena are considered. The amine solution with highest loading CO2 capacity and the effects of temperature, concentration, concentration ratio and foaming can be determined from the results. Mixed amine gives the highest loading capacity compared to the single amines. For the temperature ranging from 25-40°C the absorption capacity increases as the temperature increases. Within solvent concentration of 10-30 weight percent (wt%), the absorption capacity is increased at higher solvent concentration. Primary amine has the highest foaming tendency compared to the secondary and tertiary amines.